THE APPLICATION OF THE RESPONSIBILITY PRINCIPLE IN THE MANAGEMENT OF TANNERY IN SUKAREGANG KAB. GARUT CONNECTED WITH LAW REGULATIONS - Ghausya Syafanah Syifa (Universal Journal, 2021)
The principle of responsibility is one of the principles contained in GOOD Corporate Governance, which means that every company or business actor has a responsibility for the welfare of the community and also the environment. This GCG system has also been implemented and implemented in every region in Indonesia, especially in Garut Regency which has been listed in its regional regulations. The problem in this study is how the principle of responsibility is applied to the tannery business actors in Sukaregang Garut according to the laws and regulations and how the sanctions are applied to the tannery management business actors which cause environmental pollution in the long term. The approach method used in this research is normative juridical. The main data of this research is library data and data analysis used by the writer is by using qualitative analysis. It is concluded that the principle of responsibility which is contained in the regulations of the District Regional Regulation. Garut No. 16 of 2017 concerning Corporate Social and Environmental Responsibility has not been fully implemented properly in the Sukaregang Garut area and there are administrative and criminal sanctions if there are business actors who do not comply with these regulations.